In situ polymerized Fe2O3@PPy/chitosan hydrogels as a hydratable skeleton for solar‐driven evaporation. Issue 8 (17th April 2022) - Wang, Jinping; Shamim, Tariq; Arshad, Naila; Irshad, Muhammad Sultan; Mushtaq, Muhammad Naveed; Zhang, Chuankun; Yousaf, Muhammad; Alshahrani, Lina Abdullah; Akbar, M.; Lu, Yuzheng
Abstract: The world population is severely affected by water scarcity, and it is an alarming issue that needs to be addressed urgently. Seawater desalination by solar‐driven evaporation is a promising technique to produce clean water. However, it is energy intensive and directs to a low water yield under natural sunlight. Therefore, the developments of new photothermal materials can reduce required energy for desired evaporation rates for efficient freshwater yield. Indeed, chitosan and polypyrrole‐based polymers are natural cationic copolymers, and their nanocomposites present well deal of interest for hydrogel structures due to their hydratable skeletons, and solar‐absorbing nature. Here, we report in situ polymerized Fe2 O3 @PPy/chitosan hydrogels as lightweight evaporation structures for solar‐powered evaporation under brine solutions (3.5 wt%). The polymeric network of Fe2 O3 @PPy/chitosan hydrogels builds in cross‐linked macroporous water channels, self‐floating, and a wide range of omnidirectional solar absorption (96%). The state‐of‐the‐art evaporation experiments demonstrate an efficient evaporation rate of water (1.80 kg m –2  h –1 ) and enhanced solar‐to‐vapor conversion efficiency (91%) as compared to other carbon‐based evaporation structures, excluding heat losses under 1 kW m –2 (one sun). Of note, the ultra‐black hydrogel surface stored enough thermal energy (39.6°C) under one sun solar irradiance due to the cationic polymeric network of Fe2 O3 @PPy/chitosan. A single‐step process for a freshwater supply that has been purified from various contaminants shows the potential of this device for real‐world applications. Abstract : A ceramics‐inspired Fe2 O3 @PPy/chitosan hydrogels for synchronous seawater desalination demonstrate an excellent surface temperature (39.6°C) and an evaporation rate of 1.80 kg m −2  h −1 (91% solar‐to‐vapor generation efficiency) under one sun only. A single‐step process for a freshwater supply that has been purified from various contaminants shows the potential of this device for real‐world applications.